IFRS ADOPTION AND VALUE RELEVANCE OF ACCOUNTING INFORMATION IN NIGERIA - Uwuigbe, Uwalomwa; Uwuigbe, Olubukola Ranti; Durodola, Moyosore Esther; Jafaru, Jimoh; Jimoh, Rehimetu (International Journal of Economics and Financial Issues, 2017)
This paper examined the impact of IFRS adoption on the value relevance of accounting information in Nigeria. In achieving the objectives of this research, the fact book and the annual reports for the period 2010 -2013 were used. Also, using the judgmental sampling technic a total of ten (10) companies were selected from a population of twenty-six (26) listed companies in the consumer goods industry listed on the floor of the Nigerian Stock Exchange (NSE). The Ohlson model was adopted to develop six models for the course of the paper. Using Ordinary Least Square (OLS) regression, the study found out that; earnings per share and book value of equity per share are accounting variables that jointly explains share price. The study observed that with the introduction and adoption of IFRS, there has been is an improvement in the value relevance of accounting information. The study also observed that earnings per share exhibits a stronger explanatory power both in pre and post IFRS adoption periods. The paper therefore concludes that though IFRS has helped in the relevance of accounting information; there are still room for earnings management. Keywords: Value relevance, Accounting information, Explanatory power, IFRS, Earnings per Share JEL Classifications: G21, M41